Synergic effect of nano-catalyst and continuous flow system: Dakin–West reaction catalyzed by Nafion-H@SPIONs in a microreactor - Narei, Zahra Arabloo; Shafiee, Behnaz; Khosropour, Ahmad R. (RSC advances, 2015)
The expansion of practical processes for superferromagnetic nanocatalysts is a very attractive subject. In this work, we successfully developed a new and efficient procedure with combination of continuous flow technology with immobilizing of only 0.35 mol% of Nafion-H on silica-encapsulated supperparamagnetic iron oxide nanoparticles (SPIONs) to maximize catalyst efficiency for the synthesis of β-acetamido ketones. The turnover frequency value varies in the range of 1336 to 1577 h −1 compared to 256–515 h −1 in the conventional stirred reactor. Moreover, the catalyst could be quickly recovered by external magnetic field and could be reused for several reaction cycles without any change in its catalytic activity.